2019
DOI: 10.1101/587014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Progressive recruitment of distal MEC-4 channels determines touch response strength inC. elegans

Abstract: Through experiment and simulation, Katta, et al. reveal that pushing faster and deeper recruits more and more distant mechano-electrical transduction channels during touch. The net result is a dynamic receptive field whose size and shape depends on tissue mechanics, stimulus parameters, and channel distribution within sensory neurons. AbstractTouch deforms, or strains, the skin beyond the immediate point of contact. The spatiotemporal nature of the strain field induced by touch depends on the mechanical proper… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Such global changes in strain are too slow to activate the TRNs ( Eastwood et al. , 2015 ; Katta et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such global changes in strain are too slow to activate the TRNs ( Eastwood et al. , 2015 ; Katta et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2004 ; Cueva et al. , 2007 ; Katta et al. , 2019 ), but are disrupted in ECM mutants ( Emtage et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To learn more, we directly recorded MRCs in control and nid-1 mutant mutants. To optimize our ability to detect a partial loss-of-function, we used an ultrafast mechanical stimulator that evokes currents that are approximately five-fold larger than those evoked by slower stimuli (Katta et al, 2019). Using this approach, we found that MRCs were qualitatively similar in nid-1 mutants and wild-type controls (Figure 5H), but that MRCs were smaller in nid-1 mutants (Figure 5I).…”
Section: Mechanosensory Complexes Assembly Depends On Nidogen and Lam...mentioning
confidence: 99%